A noninvasive smart wearable for diaper moister quantification and notification - Tareq Khan (Institute of Advanced Engineering and Science, 2019)
A baby feels uncomfortable in a wet diaper and it can cause health issues such as diaper rash. Diaper rash can be avoided by changing the diaper as soon as the baby urinates or passes stool. In this project, a smart wearable gadget is developed which sends an automatic notification to a caregiver’s smartphone whenever the baby urinates. The proposed wearable detects urination event noninvasively by sensing the temperature rise on the outer surface of the diaper and quantifies the event using a decision tree and a midpoint based k-nearest neighbor (KNN) hybrid classification algorithm. The gadget is a small size, low power, low cost and reusable electronic device that is attached externally to the outer surface of the diaper. The gadget can be used with any disposable diaper, thus no change in the diaper production process or price increase is required. The smartphone app shows the diaper change urgency score and logs all the urination events. This record can facilitate treating diseases where accurate records of urination are required. A prototype of the hardware gadget and a smartphone app is developed and tested.